Temporal relationship between body mass index and uric acid and their joint impact on blood pressure in children and adults: the Bogalusa Heart Study - Yun, Miaoying (Int J Obes (Lond), 2021)
OBJECTIVE: This study aimed to examine the temporal relationship between body mass index (BMI) and uric acid (UA), and their joint effect on blood pressure (BP) in children and adults. METHODS: The longitudinal cohorts for temporal relationship analyses consisted of 564 and 911 subjects examined twice 5–14 years apart from childhood to adulthood. The cross-sectional cohorts for mediation analyses consisted of 3102 children and 3402 nondiabetic adults. Cross-lagged panel analysis models were used to examine the temporal relationship between BMI and UA, and mediation analysis models the mediation effect of UA on the BMI–BP association. RESULTS: After adjusting for age, race, sex and follow-up years in children, and additionally smoking and alcohol drinking in adults, the path coefficients (standardized regression coefficients) from baseline BMI to follow-up UA (0.145 in children and 0.068 in adults) were significant, but the path coefficients from baseline UA to follow-up BMI (0.011 in children and 0.016 in adults) were not. In mediation analyses, indirect effects through UA on the BMI-systolic BP association were estimated at 0.028 (mediation effect = 8.8%) in children and 0.033 (mediation effect = 13.5%) in adults (P < 0.001 for both). Direct effects of BMI on systolic BP (0.289 in children and 0.212 in adults) were significant. The mediation effect parameters did not differ significantly between Blacks and Whites. CONCLUSIONS: Changes in BMI precede alterations in UA, and the BMI–BP association is in part mediated through BMI-related increase in UA both in children and in adults. These findings have implications for addressing mechanisms of obesity hypertension beginning in early life.